Camille Ben Ziad and his Place in the Arab-Islamic Heritage (Historical Study) - Raghad Jamal Manaf Al - Azzawi (College of Education for Women, 2018)
In a quick reading of the character of Camille Ben Ziad al-Nekha al-Kufi al-Taabi, one of the most sincere companions of Imam Ali (peace be upon him), he enjoyed great status and status because he was one of the people of his people who lived alongside Imam Ali (peace be upon him) since his tribe migrated from Yemen to Kufa To this end, he became loyal during the reign of Imam Ali (peace be upon him), who is also a member of the delegation coming from Kufa to protest against the actions of the Wali of Kufa during the reign of Caliph Uthman ibn Affan. After the death of Caliph Uthman bin Affan, (Peace and blessings of Allaah be upon him) (Duaa kamil), one of the most famous and important supplications in Islamic history, and each one of us who hears du'aa 'is heartfelt. The scholars have described it with several descriptions: "He is the bearer of the secret of Imam Ali (peace be upon him) Kamil bin Ziyad's position in the Arab-Islamic heritage lies in the internal events of the Islamic state during the reign of the Caliph Uthman ibn Affan, and the fact that he participated with Imam Ali (peace be upon him) in the Battle of Gamal, Safin and Nahrawan, and knew that he was honest and obedient In his people, and then Imam Ali (peace be upon him) working on the house of Alma As well as his role in the protection of the city of Hit when he was the guardian of it and hence began to address the attempts of Muawiya, which was aimed at controlling the areas under the rule of Imam Ali (peace be upon him), he continued to loyalty and love to the house of the Prophet, (Peace be upon him) after the persecution of his father, the Hajjaj bin Yusuf Al-Thaqafi was killed during the reign of Marwan bin al-Hakam, Kamil bin Ziyad year (82 e) after the request in his request was forced to surrender himself to the pilgrims after his famous saying "I am a great Sheikh has fed "The pilgrims hit his neck and were buried in the back of Kufa in an area called Al-Thawba near Of Najaf